Oral Misoprostol for Induction of Labor - Seth, Shikha; Nagrath, Arun; Goel, Neeru (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i1.5060 NJOG 2010 Jul-Aug; 5(1): 40-43